Quality and food safety management review: Biblioshiny - Bingqing Zhu; Qasim Hamakhurshid Hamamurad; Hayati Habibah Abdul Talib (CyTA - Journal of Food, 2024)
Economic and population growth has globalised the food industry. Researchers have not yet reached a consensus on the most complicated QFSM practices in the food industry. Our study uses Biblioshiny to analyse 820 articles on QFSM to fill a research gap and 87 articles from a systematic literature review (SLR) to identify the Critical Success Factors for Food Safety Management. Publications from Dimensions, Scopus, and the Web of Science databases provide an unbiased view of research status from 1974 to April 2024. The review of QFSM recorded 3042 authors from 57 countries or regions. Our research identifies over 20 critical success factors for food safety management, highlighting the link between food safety, quality management, and supply chain resilience in the food industry, and our study presents the impact of The COVID-19 epidemic, which has changed consumer behaviour and company expectations, presenting new food sector problems.